2020
DOI: 10.1097/sih.0000000000000524
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Cycle Deliberate Practice Simulation Curriculum Improves Pediatric Trauma Performance

Abstract: Introduction: Simulation-based medical education allows learners to refine and maintain clinical skills especially for high-stake situations such as trauma resuscitation. Despite the primary and secondary survey being its foundation, literature shows poor adherence with overall rates as low as 13%. This study evaluates the impact of rapid cycle deliberate practice (RCDP) on primary and secondary survey skill retention. We hypothesized that RCDP-trained surgery residents will have real-world clinical improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
(63 reference statements)
1
3
0
Order By: Relevance
“…Our findings are in line with existing research on RCDP, which has shown improved performance of teams 15,17,18,32‐35 . This project showed that time to defibrillation was shorter when teams were trained using RCDP compared with PSD.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are in line with existing research on RCDP, which has shown improved performance of teams 15,17,18,32‐35 . This project showed that time to defibrillation was shorter when teams were trained using RCDP compared with PSD.…”
Section: Discussionsupporting
confidence: 91%
“…RCDP has been shown to improve skills in simulation settings 10,14,16–21 ; however, to our knowledge, prior to this study there has been limited evidence for translation to actual patients. One study assessed examination performance during patient care via video review compared to the simulation setting, 36 while another showed improved care in the simulation setting pre‐ and post‐RCDP airway management training but found no improvement in intubation success 17 . Our study is unique both in the creation of a novel airway training program and in demonstrating improved clinical outcomes for the patients who were intubated by trainees who participated in the program.…”
Section: Discussionmentioning
confidence: 84%
“…4 We have performed RCDP has been shown to improve skills in simulation settings 10,14,[16][17][18][19][20][21] ; however, to our knowledge, prior to this study there has been limited evidence for translation to actual patients. One study assessed examination performance during patient care via video review compared to the simulation setting, 36…”
Section: Discussionmentioning
confidence: 99%
“… 11 RCDP simulation training in pediatric trauma has demonstrated participant improvement not just in the practice setting but also in actual patient care. 12 …”
Section: Introductionmentioning
confidence: 99%